A new Calliprora species mining lead trees in Florida (Lepidoptera: Gelechiidae) - Lee, Ga-Eun; Hayden, James E. (Zootaxa, 2019)
Calliprora leucaenae sp. nov. is described infesting foliage of Leucaena leucocephala (Lam.) de Wit. in Florida, USA. The larvae are blotch-miners and leaf-tiers and are capable of heavy damage to host plants. Photographs of the adult, wing venation, male and female genitalia and illustrations of the larval and pupal chaetotaxy are provided. Calliprora Meyrick is transferred to Thiotrichinae, as the species in the genus exhibit typical characters of the subfamily such as the presence of anellus lobes, a large sternum VIII, and a reduced male tergum VIII. Comparative diagnoses of the morphology and ecology are presented for the newly described species and other thiotrichine species.